O discurso das diferenças: análise do interdiscurso, do ethos e da cenografia em A cidade e a infância de José Luandino Vieira - Santos, Elaine Ferreira dos (2015)
The theme of this thesis is focused on the analysis of literary discourse, more specifically as regards the interdiscourse, the construction of scenography, the discursive ethos in the discourse "A cidade a a infância" the writer Jose Luandino Vieira. In the case of this discourse, the interlocution retrieves elements originated from the social world, represented by history and recounted in the discourses. The guiding question in this study was defined as follows: the speeches, Jose Luandino Vieira, allow you to describe and analyze the discursive ethos considering the particularities of literary writing with regard to the situation of enunciation, particularly the scenography built in the various listed in wire discursive scene. The concept of ethos helps us to think about the process of accession of the subjects to the point of view that is defended in the speeches, especially in literary discourse